(untitled) (Journal of actual problems of jurisprudence, 2018)
The ecological situation is gradually becomes more important factor of development, which affect to all area of political and economic well-being of the state. In the third millennium, the world is changing more rapidly, and the joint action of the state which protect environment, often fall behind economic and social change. Gradually, to the economy of the CIS countries penetrate the environmental standards of developed countries. Using rich natural resources of Kazakhstan, rapid development of the economy in recent years, needs to train specialists which able to solve problems of the environment. Today environmental problems of the Republic of Kazakhstan are difficult, protean and territorial differentiated. Emission of harmful substances into the atmosphere from stationary sources in the country is in the top of three, which accounts for more than half of the emissions of all the CIS countries after Russia and Ukraine. According to the volume of polluted wastewater, Kazakhstan also took 3rd place, but in 2005 he step back this doubtful privilege to Azerbaijan. Key words: The environmental problems, the environment, the environmental regions ecological culture.